1992
DOI: 10.1111/j.1751-1097.1992.tb08508.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiationless Deactivation and Fluorescence of Selected Pyridones

Abstract: Numerous 3-position derivatives of 2-hydroxy pyridine, also known as 2-pyridone, were synthesized and their optical absorption and fluorescence spectra examined. The quantum yield of emission varied from near zero to near unity depending on the kind of substitution made and the solvent. Data are presented that argue for the T-T' nature of the first excited state in all cases. It was concluded that intramolecular hydrogen bonding controls the extent of internal conversion and hence the amount of fluorescence. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Experimentally it has been observed that the absorption maximum of CD is at 360 nm. It has been shown in the literature that 2-pyridone derivatives exhibit emission maximum at around 380 nm. Experimentally we observed that the emission maximum of CD is at around 450 nm. Thus, we observed an emission maximum which is 80 nm Stokes shifted.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Experimentally it has been observed that the absorption maximum of CD is at 360 nm. It has been shown in the literature that 2-pyridone derivatives exhibit emission maximum at around 380 nm. Experimentally we observed that the emission maximum of CD is at around 450 nm. Thus, we observed an emission maximum which is 80 nm Stokes shifted.…”
Section: Resultssupporting
confidence: 56%
“…As there is no significant change in the dipole moment (see orbital electron cloud picture (HOMO–LUMO plot) in Figure S7, Supporting Information) from the ground state to the excited state, no significant red shift of the emission maximum is expected; indeed, we could observe no change of the emission maximum on changing the polarity or proticity of the medium (on moving from ACN to MeOH to water) (Figure S8, Supporting Information). Literature results show that the excited state lifetime of 2-pyridone derivatives is around 5 ns in alcoholic solvents and around 8 ns in aqueous medium. Experimentally it has been observed that our CDs exhibit single-exponential PL decay with an excited state lifetime of CD around 10 ns in methanol and around 15 ns in aqueous medium (Figure S9 in Supporting Information). Thus, the fluorescence lifetime of our CD (similar to emission maximum) is higher than literature reports for 2-pyridone derivatives (Figure , Table ).…”
Section: Resultsmentioning
confidence: 67%
“…We speculate that excited state protonation induces greater sp3 character on this carbonyl group, resulting in loss of planarity and rigidity of the conjugated 2-pyridone system since the C-5 carbon has significant atomic orbital (AO) contributions in the excited state (Supplementary Section C). This induces out-of-plane vibrations that draw pathways to non-radiative relaxation, a dynamic quenching mechanism commonly reported for heterocyclic aromatics 26-28 . Collectively, proton-induced dynamic quenching is primarily attributed to excited state protonation of the 5-carbonyl, which cannot occur until both the 7- and 3-carboxylates are protonated (below pH 3.4 and 2.4 respectively).…”
Section: Resultsmentioning
confidence: 92%
“…This induces out-of-plane vibrations that draw pathways to non-radiative relaxation, a dynamic quenching mechanism commonly reported for heterocyclic aromatics. 26 28 Collectively, proton-induced dynamic quenching is primarily attributed to excited state protonation of the 5-carbonyl, which cannot occur until both the 7- and 3-carboxylates are protonated (below pH 3.4 and 2.4 respectively). In support of this model, the SV-plot of fluorescence lifetimes show an abrupt linearity (indicating dynamic quenching) just below pH 2.3 (ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 2-pyridone ring is one of the most classes of fluophores, with several photo functional applications [18], this skeleton exhibit a strong emission in different regions of spectrum. Recently, they are a much interest in the development of convenient methodologies of the synthesis of 2-pyridones from simple and available starting materials to their fluorescent properties [19][20][21].…”
Section: Introductionmentioning
confidence: 99%